A KSHV-targeted small molecule efficiently blocks SARS-CoV-2 infection via inhibiting expression of EGFR and Cyclin A2 - Zhongwei Dong; Xinyu Wang; Gaowei Hu; Qingye Huang; Yulin Zhang; Yuping Jia; Shujuan Du; Caixia Zhu; Fang Wei; Daizhou Zhang; Yuyan Wang; Qiliang Cai (Emerging Microbes and Infections)
The Coronavirus Disease 2019 (COVID-19) pandemic has led to numerous cases of co-infection with SARS-CoV-2 and other viruses, including Kaposi’s sarcoma-associated herpesvirus (KSHV), worldwide. This co-infection has increased patient mortality due to the lack of efficient bi-targeted drugs. Cambogin, a bioactive natural product, has been shown to effectively induce regression of KSHV-latently infected tumours in xenograft mice models; however, its impact on SARS-CoV-2 infection remains unclear. Here, we report that Cambogin targets 46 host genes commonly affected by both SARS-CoV-2 and KSHV infections, as identified through bioinformatics analysis. These genes are related with 14 key upstream signalling pathways, particularly those involved in inflammation regulation, protein phosphorylation, metabolic processes, and cellular stress response. Within the transcriptional factor (TF)-miRNA co-regulatory network, ten out of 46 hub-target genes are closely linked to Cambogin and KSHV/SARS-CoV-2. Importantly, Cambogin not only efficiently blocks the replication and virion production of SARS-CoV-2 in vitro and in vivo by reducing the expression of EGFR and Cyclin A2, but also simultaneously inhibits both SARS-CoV-2 infection and the growth of KSHV-induced tumours in vivo using a murine xenograft model. These findings provide an alternative strategy for the potential use of Cambogin in the treatment of SARS-CoV-2 patients, particularly those with KSHV co-infection.